2008
DOI: 10.12968/ijtr.2008.15.10.31213
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of community-based rehabilitation programmes for adults with TBI

Abstract: Aims: The aim of this systematic review was to investigate the factors that infl uence the efficacy of community-based rehabilitation programmes in improving the quality of life and daily functioning of adults with severe traumatic brain injury. Methods: A systematic review of the literature was conducted. In keeping with the principles of best evidence synthesis, the findings from the studies were analysed according to their methodological quality. Findings: Eleven studies were included in the review; synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…A range of community-based TBI rehabilitation programs have been explored and include interdisplinary team rehabilitation (Ponsford et al, 2006;Ponsford, Oliver, & Nelms, 2003;Powell, Heslin, & Greenwood, 2002;Smith et al, 2006), home based behavioral management program (Carnevale, Anselmi, Busichio, & Millis, 2002;Carnevale, Anselmi, Johnston, Busichio, & Walsh, 2006), outdoor experiential education programs (Thomas, 2004;Walker, Onus, Doyle, Clare, & McCarthy 2005), telephone counseling (Bell et al, 2005), client and caregiver educational training program (Sinnakaruppan, Downey, & Morrison, 2005) and community-based peer support (Hibbard et al, 2002). While the efficacy of these programs depended on an interaction of program and participant characteristics, and the methods used to assess outcomes (Evans & Brewis, 2008), the greatest treatment effects were seen in quality of life and functional independence measures and were associated with interdisplinary team rehabilitation programs as, telephone counseling, educational group training, and a group outward bound course. Overall, those programs that involved group interventions, demonstrated greater treatment effects than those involving individual therapy programs on measures of quality of life and functional independence (Evans & Brewis, 2008).…”
Section: Psychotherapeutic Approaches To the Treatment Of Tbimentioning
confidence: 99%
See 3 more Smart Citations
“…A range of community-based TBI rehabilitation programs have been explored and include interdisplinary team rehabilitation (Ponsford et al, 2006;Ponsford, Oliver, & Nelms, 2003;Powell, Heslin, & Greenwood, 2002;Smith et al, 2006), home based behavioral management program (Carnevale, Anselmi, Busichio, & Millis, 2002;Carnevale, Anselmi, Johnston, Busichio, & Walsh, 2006), outdoor experiential education programs (Thomas, 2004;Walker, Onus, Doyle, Clare, & McCarthy 2005), telephone counseling (Bell et al, 2005), client and caregiver educational training program (Sinnakaruppan, Downey, & Morrison, 2005) and community-based peer support (Hibbard et al, 2002). While the efficacy of these programs depended on an interaction of program and participant characteristics, and the methods used to assess outcomes (Evans & Brewis, 2008), the greatest treatment effects were seen in quality of life and functional independence measures and were associated with interdisplinary team rehabilitation programs as, telephone counseling, educational group training, and a group outward bound course. Overall, those programs that involved group interventions, demonstrated greater treatment effects than those involving individual therapy programs on measures of quality of life and functional independence (Evans & Brewis, 2008).…”
Section: Psychotherapeutic Approaches To the Treatment Of Tbimentioning
confidence: 99%
“…While the efficacy of these programs depended on an interaction of program and participant characteristics, and the methods used to assess outcomes (Evans & Brewis, 2008), the greatest treatment effects were seen in quality of life and functional independence measures and were associated with interdisplinary team rehabilitation programs as, telephone counseling, educational group training, and a group outward bound course. Overall, those programs that involved group interventions, demonstrated greater treatment effects than those involving individual therapy programs on measures of quality of life and functional independence (Evans & Brewis, 2008).…”
Section: Psychotherapeutic Approaches To the Treatment Of Tbimentioning
confidence: 99%
See 2 more Smart Citations
“…These reviews have focussed on evaluating interventions enabling community integration [3], assessing the effects of multi-disciplinary rehabilitation [4] and exploring the efficacy of rehabilitation interventions delivered in community settings [5]. Turner Stokes et al [4] concluded that people with ABI should have access to outpatient or community-based services appropriate to their needs.…”
mentioning
confidence: 99%